2021
DOI: 10.1136/bmjopen-2020-041512
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance and acceptability of self-collected vaginal and urine samples compared with clinician-taken cervical samples for HPV testing among women referred for colposcopy. A cross-sectional study

Abstract: ObjectivesTo increase effectiveness of the cervical cancer screening program, self-sampling can be an option. Both self-collected vaginal samples (SCV) and urine samples may be useful alternatives to clinician-taken cervical samples (CS).DesignCross-sectional study.SettingColposcopy clinic.ParticipantsWomen (n=305) referred to colposcopy after abnormal cervical screening result or conditions like postcoital bleeding.InterventionAll women self-collected a urine and a vaginal sample prior to colposcopy, where a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 44 publications
5
37
1
Order By: Relevance
“…A disadvantage of this study however is that no paired cervical specimen was available to report relative clinical accuracy estimates compared to clinician-collected samples. In their cross-sectional study, Ørnskov (2021) demonstrated both noninferior clinical sensitivity (CIN2+; CIN3+) and specificity (<CIN2) of hrHPV testing in urine collected in a simple urine cup compared to clinician-collected cervical samples [38]. This clinical validation is promising and first to demonstrate both non-inferior clinical sensitivity and specificity for urinary hrHPV testing compared to cervical samples collected by a physician.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A disadvantage of this study however is that no paired cervical specimen was available to report relative clinical accuracy estimates compared to clinician-collected samples. In their cross-sectional study, Ørnskov (2021) demonstrated both noninferior clinical sensitivity (CIN2+; CIN3+) and specificity (<CIN2) of hrHPV testing in urine collected in a simple urine cup compared to clinician-collected cervical samples [38]. This clinical validation is promising and first to demonstrate both non-inferior clinical sensitivity and specificity for urinary hrHPV testing compared to cervical samples collected by a physician.…”
Section: Discussionmentioning
confidence: 96%
“…The presented FV urine method is also complementary to high-throughput, automated Abbott RealTime High Risk HPV testing without the need for additional laborious sample handlings steps such as preservative addition or centrifugation reported by others [13,37,38]. Colli-Pee collected, UCM preserved FV urine allows for sample handling following the same procedure applied for manufacturer validated cervical samples collected by a clinician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 119 Ørnskov et al found absolute sensitivity for CIN2 + of urine and vaginal self-samples was comparable to cervical clinician-collected samples (93% for urine samples and 96% for self-collected samples). 122 Furthermore, a majority of studies of HPV testing on urine samples have noted lower hrHPV positivity than corresponding vaginal samples. 118 , 120 , 123–125 …”
Section: Types Of Devices For Hpv Self-samplingmentioning
confidence: 99%
“…This may consequently lead to an increase in attendance and effectiveness of cervical cancer screening ( Tranberg et al, 2020 ). Especially urine collection looks promising as it has been reported as the most preferred sampling method for cervical cancer screening in several studies ( Leeman et al, 2017 , Ørnskov et al, 2021 , Rohner et al, 2020 , Sargent et al, 2019 , Tranberg et al, 2020 ). However, urine collection methods differ in these studies and few studies have compared the collection of complete urine void without special devices to cervicovaginal self-sampling in a home-based setting ( Leeman et al, 2017 , Ørnskov et al, 2021 , Rohner et al, 2020 , Sargent et al, 2019 , Tranberg et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%